Endocrine FGFs: Evolution, Physiology, Pathophysiology, and Pharmacotherapy - Itoh, Nobuyuki; Ohta, Hiroya; Konishi, Morichika (Frontiers in Endocrinology, 2015)
The human fibroblast growth factor (FGF) family comprises 22 structurally related polypeptides that play crucial roles in neuronal functions, development, and metabolism. FGFs are classified as intracrine, paracrine, and endocrine FGFs based on their action mechanisms. Paracrine and endocrine FGFs are secreted signaling molecules by acting via cell-surface FGF receptors (FGFRs). Paracrine FGFs require heparan sulfate as a co-factor for FGFRs. In contrast, endocrine FGFs, comprising FGF19, FGF21, and FGF23, require α−Klotho or β−Klotho as a co-factor for FGFRs. Endocrine FGFs, which are specific to vertebrates, lost heparan sulfate-binding affinity and acquired a systemic signaling system with αKlotho or βKlotho during early vertebrate evolution. The phenotypes of endocrine FGF knockout mice indicate that they play roles in metabolism including bile acid, energy, and phosphate/active vitamin D metabolism. Accumulated evidence for the involvement of endocrine FGFs in human genetic and metabolic diseases also indicates their pathophysiological roles in metabolic diseases, potential risk factors for metabolic diseases, and useful biomarkers for metabolic diseases. The therapeutic utility of endocrine FGFs is currently being developed. These findings provide new insights into the physiological and pathophysiological roles of endocrine FGFs and potential diagnostic and therapeutic strategies for metabolic diseases.